Effects of natural menopause, hysterectomy, and oophorectomy on lumbar spine and femoral neck bone densities - Hreshchyshyn, M M; Hopkins, A; Zylstra, S; Anbar, M (Obstetrics and gynecology (New York. 1953), 1988)
Lumbar spine and femoral neck bone densities of women, aged 35-65, were measured by dual photon bone densitometry. After exclusion of women with spinal and other abnormalities, this study included 233 subjects: 60 menstruant, 91 who underwent natural menopause (56 more than 2 years post-menopause), 45 bilaterally oophorectomized, and 37 hysterectomized without bilateral oophorectomy. No significant differences were found between the age-normalized average bone densities of the menstruant, early postmenopausal, and late postmenopausal women; nor was there a difference between the rates of their bone loss. The bone densities of the hysterectomized women were significantly lower than those of the normals. The bone densities of the oophorectomized women were significantly lower than those of the hysterectomized patients. The rates of bone loss, however, were comparable in all groups studied. The use of estrogen without progestin was associated with significantly higher lumbar spine densities in the oophorectomized women, but showed no significant effect in any of the other groups.